2004
DOI: 10.1099/jmm.0.45528-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between real-time PCR, conventional PCR and different staining techniques for diagnosing Pneumocystis jiroveci pneumonia from bronchoalveolar lavage specimens

Abstract: bronchoalveolar lavage (BAL) specimens from 150 patients (19 HIV-infected and 131 non-HIV-infected patients) were evaluated for identification of Pneumocystis jiroveci (formerly known as Pneumocystis carinii f. sp. hominis) using staining techniques, conventional PCR (mtLSUrRNA gene) and real-time PCR (MSG gene). Test results were compared to Pneumocystis pneumonia (PCP) confirmed by typical clinical findings and response to treatment. Sensitivity and specificity of the techniques were 60 and 100 % for stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
142
2
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(152 citation statements)
references
References 19 publications
4
142
2
4
Order By: Relevance
“…The difference between semi-Q RT-PCR and quantitative RT-PCR is well recognized [25] ; however, as much of the information related to neurotrophin mRNA expression in the striatum was obtained with semi-Q RT-PCR or in situ hybridization, we used this as a reference for comparison with previous reports in the same region [3][4][5] . We are aware that the primers used in the present study were designed for semi-Q RT-PCR [20,21] .…”
Section: Semi-q Pcr Versus Quantitative Rt-pcr Thementioning
confidence: 99%
See 1 more Smart Citation
“…The difference between semi-Q RT-PCR and quantitative RT-PCR is well recognized [25] ; however, as much of the information related to neurotrophin mRNA expression in the striatum was obtained with semi-Q RT-PCR or in situ hybridization, we used this as a reference for comparison with previous reports in the same region [3][4][5] . We are aware that the primers used in the present study were designed for semi-Q RT-PCR [20,21] .…”
Section: Semi-q Pcr Versus Quantitative Rt-pcr Thementioning
confidence: 99%
“…this does not always correspond to the optimal efficiency of the reaction and therefore is less precise [25] .…”
Section: Neurotrophinmentioning
confidence: 99%
“…However, lack of standardization and clinical validation of the laboratory-developed assays is the primary reason why the EORTC/MSG group decided to omit all fungal PCR from the definitions of invasive fungal diseases (7). In addition, several papers attest to the fact that PCR diagnosis of PCP is more sensitive than microscopy (4,10,11,13,22,24). The generally higher sensitivity of PCR assays than of microscopy may be disproportionately important for non-AIDS patients and may result in fewer missed clinical diagnoses.…”
mentioning
confidence: 99%
“…In particular, results might differ between HIV-positive and -negative cases. Such a difference has been found in previous studies, which have indicated the difficulty of confirming a PCP diagnosis in non-HIV-infected cases due to the lack of sensitivity of PCR methods (20-25%), even in BAL specimens [5,23,25,32]. The PCR positive rate for PCP in the HIV positive patients was higher than that in the HIV negative patients (6/8:75%>2/8:25%) [7].…”
Section: Quantitative Pcr Total Samples (Sputum and Bal)mentioning
confidence: 38%
“…It is thought that real-time PCR, as recently described [5,14], might be useful in distinguishing between colonization and clinical disease. This sugges-tion is based on the hypothesis that PCP patients should have a higher organism burden than colonized or subclinically infected patients, and that this would be reflected by a higher amount of Pneumocystis jiroveci DNA present in the extracted specimens from PCP patients.…”
Section: Pneumocystis Jiroveci Formerly Known Asmentioning
confidence: 99%